Exercise testing in patients with asymptomatic moderate or severe aortic stenosis. Issue 22 (13th April 2018) - Saeed, Sahrai; Rajani, Ronak; Seifert, Reinhard; Parkin, Denise; Chambers, John Boyd
Abstract : Objective: To assess the safety and tolerability of treadmill exercise testing and the association of revealed symptoms with outcome in apparently asymptomatic patients with moderate to severe aortic stenosis (AS). Methods: A retrospective cohort study of 316 patients (age 65±12 years, 67% men) with moderate and severe AS who underwent echocardiography and modified Bruce exercise treadmill tests (ETTs) at a specialist valve clinic. The outcome measures were aortic valve replacement (AVR), all-cause mortality or a composite of AVR and all-cause mortality. Results: At baseline, there were 210 (66%) patients with moderate and 106 (34%) with severe AS. There were 264 (83%) events. 234 (74%) patients reached an indication for AVR, 145 (69%) with moderate and 88 (83%) with severe AS (p<0.05). Of the 30 (9%) deaths recoded during follow-up, 20 (67%) were cardiovascular related. In total, 797 exercise tests (mean 2.5±2.1 per patient) were performed. No serious adverse events were observed. The prevalence of revealed symptoms at baseline ETT was 29% (n=91) and was significantly higher in severe AS compared with moderate AS (38%vs23%, p=0.008). Symptoms were revealed in 18%–59% of patients during serial ETT conducted over a follow-up period of 34.9 (SD 35.1) months. The event-free survival at 24 months with revealed symptoms was 46%±4% and without revealed symptoms was 70%±4%. Conclusions: ETT in patients with moderate or severe AS is safe and tolerable. Serial exercise testing is useful to reveal symptoms not volunteered on the history and adds incremental prognostic information to baseline testing.